Access and use of the oral health service in a reference center in oral cleft in the state of Bahia - Juliana Alves BARBOSA; Beatriz Maia Medrado de ARAÚJO; Liliane Akemi Kawano SHIBASAKI; Alena Ribeiro Alves Peixoto MEDRADO; Silvia Regina de Almeida REIS (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT This study aimed to determine the access and utilization of dental services in a reference center for orofacial defects in the state of Bahia, Brazil. In an interview, a questionnaire was done about socio-demographic information, cleft type, specialized treatments, scheduling time and return of the consultation of 101 patients with nonsyndromic cleft lip with or without cleft palate and 101 healthy controls. In both groups the age was between 5 to 12 years old. It was observed that individuals with cleft had faster access to the dental service in relation to the control group and shorter scheduling time between the first consultation and their return. Different needs in the use of dental services were observed in the study groups with differences in relation to the specialties (p=0.000). The nonsyndromic cleft lip with or without cleft palate individuals showed socialization difficulties in the age group between 9 and 12 years and did not present difficulties in accessing primary dental care in specialized service. In conclusion, in this study NSCL±P individuals did not present difficulties in accessing the specialized dental center. To complement the comprehensive care, it is suggested the performance of educational activities of oral health, not yet fully implemented in this multidisciplinary treatment center.